Liver Injury Associated with Sporting Activities - Hassan, Ammar; Fontana, Robert J. (Seminars in Liver Disease, 2018)
Exertional heat stroke most commonly develops following prolonged levels of aerobic activity in a warm or humid environment. Hypoperfusion of the vital organs along with activation of the inflammasome can lead to progressive and potentially fatal multiorgan failure including acute liver failure. In the United States, herbal and dietary supplements that are marketed to improve performance, strength, and weight loss are increasingly being used by both amateur and professional athletes. Consumption of bodybuilding supplements that contain androgenic anabolic steroids can lead to adverse hepatic effects ranging from asymptomatic serum aminotransferase elevations to severe cholestatic hepatitis with prolonged jaundice. Various non-bodybuilding nutritional supplements that contain a mixture of botanicals, caffeine, and chemicals have also been associated with idiosyncratic hepatotoxicity. In particular, green tea extract derivatives that contain epigallocatechin gallate are hepatotoxic in animal models and have been associated with severe acute hepatocellular injury in humans.
Keywords: hepatotoxicity; herbal and dietary supplements; anabolic steroids; heat stroke